INTRODUCTION: HOMAGE À WALTER FREEMAN III. - Nualláin, Seán O. (Cosmos & History, 2016)
The article discusses the conference titled "Reparsing Nature: Science as if Being Mattered" focusing on causal explanation at each level of nature including teleology in biology.